Rheumatic heart disease: pilot study for a population-based evaluation of prevalence and cardiovascular outcomes among schoolchildren in Nepal. Issue 5 (19th October 2012) - Shrestha, Nikesh Raj; Kalesan, Bindu; Karki, Prahlad; Sherpa, Kunjang; Basnet, Anil; Urban, Philip; Pilgrim, Thomas
Abstract : Objectives: To evaluate a protocol for a population-based programme targeting the prevention of rheumatic heart disease (RHD) progression by early echocardiographic diagnosis of valvular lesions and timely implementation of secondary prevention. Design: Observational survey with a subsequent prospective cohort study. Setting: Private boarding school in the urban area of the Sunsari district situated on the foothills of the Lower Himalayan Range in Eastern Nepal. Participants: Fifty-four unselected school-going children 5–15 years of age, 24 girls and 30 boys. Primary outcome measure: Logistic feasibility of a large-scale population-based screening study using the echocardiographic criteria formulated by the World Heart Federation, with longitudinal follow-up of children with definite or borderline RHD in a prospective cohort study. Results: Standardised interview, physical examination and screening echocardiography were performed in a three-staged process and took approximately 6 min per child. Socio-economic status was assessed using surrogate markers such as the occupation of the primary caregiver, numbers of rooms at home, car, television, cell phone and internet connection. Physical examination was focused on cardiac auscultation and signs of acute rheumatic fever and targeted echocardiography was performed by an independent examiner without knowledge of the clinical findings. Two children with evidence of borderline RHD were re-examined at B.P. Koirala Institute of Health Sciences and the indication for secondary antibiotic prevention was discussed with the parents and the children. At 6 months of follow-up, echocardiographic findings were stable in both children. Implementation of secondary antibiotic prevention was challenged by impaired awareness of subclinical RHD among parents and inadequate cooperation with family physicians. Conclusions: This pilot study shows that the methods outlined in the protocol can be translated into a large-scale population-based study. We learned that education and collaboration with teachers, parents and family physicians/paediatricians will be of key importance in order to establish a sustainable programme.